Materials Selection in Teaching English Skills for Teachers of Senior High School in Serang City - Nurhaedah Gailea; Syafrizal Syafrizal; Iin Indasari (Journal of English Language Teaching and Cultural Studies, 2018)
This study aims to find out whether English teachers at Senior high schools in the City of Serang have carried out learning based on the procedures for selecting learning materials before it begins to teach. In this study, the researchers used qualitative research. The instruments of this study are observation, documentation, questionnaire, and interview. The teachers and students took part in completing questionnaires and interviews for the purpose of study.  The final goal of this study is that English teachers have certain theory and strategy in selecting materials that will be brought into classroom. The result of this study showed that the teachers designed the activities in teaching and learning based on curriculum, but most of teachers of Senior High School in Serang City did not use the theories and procedure to select the materials in teching learning process. The result also showed that the students were not interested in reading materials, and understood the reading text easily or they had low motivation in reading. To ovecome this, it needs special training for teachers, and the schools should have literature facility of self-access center.